Mapping Global Research Progress in Rice Blast Resistance Breeding: A Scientometric Analysis - Soujanya, T.; Wasudeo, N. G.; Vani, D. P. D.; Kumar, G. H. (International Journal of Bio-resource and Stress Management, 2026)
The present study was conducted during November, 2022–July, 2023 at the School of Agriculture, SR University, Warangal, Telangana, India, to analyze the global publication trends in rice blast resistance research from 2010 to 2021. Rice blast, caused by Magnaporthe oryzae, was one of the most devastating diseases affecting rice productivity worldwide, necessitating continuous research efforts in resistance breeding and disease management. A thorough literature review was done employing scientometric and network analysis methods to evaluate the growth, structure, and dynamics of research in the rice blast resistance domain. A total of 1,242 research papers indexed in the Scopus database, published during the period from 2010 to 2021, were used for the study. The mapping of the key aspects examined the following analyses: co-occurrence and co-citation. The literature data including citations, abstracts, bibliographic details, keywords, and funding information were evaluated using the VOS viewer software to generate visualization maps. The analysis helped to discover the major research institutions, leading countries, the most cited articles, the leading authors in terms of publication output and citations, and the main research sources on the blast resistance of rice. The findings of this research not only clarified the trends and contributions of the past research but also provided great support, direction and useful reference for researchers, policymakers, and academicians who would be tackling rice blast resistance.